Analysis of Rice Fields Conversion to Improve Control Strategies: A SWOT Framework - Saragih, Jef Rudiantho; Sitepu, Dhenny Valentino P. A.; Nurhayati, Nurhayati (Agro Bali : Agricultural Journal, 2024)
Rice fields are the leading supplier of rice in Indonesia. The conversion of rice fields is a severe problem that needs to be addressed to support food security. This study aims to formulate a strategy to control the conversion of rice fields in Pematangsiantar City. We conducted a comprehensive SWOT analysis, identifying the strengths, weaknesses, opportunities, and threats to control rice field conversion. This analysis was based on focus group discussions and in-depth interviews with 24 key respondents. Based on the evaluation matrix of internal and external factors and the strategy matrix, the strategies to control rice field conversion are aggressive (SO strategy), adaptive (WO strategies), and competitive (ST strategies). The main strategies are regulatory consistency, incentive, and disincentive systems, preparation of LP2B Perda, consistency in issuing non-agricultural sector permits, and institutional capacity building of rice farmers. This research is the latest comprehensive study in formulating control strategies for rice field conversion in Pematangsiantar City. The contribution is a strategy that can be used as an action program to control the conversion of rice fields. Implementing the strategy requires technical and political will from all stakeholders, especially local government, legislators, and farmers.